Cultivating Interpretation Skills in IPAS Learning at Madrasah Ibtidaiyah - Yasinta Ainur Rohmah; Sutama Sutama (FKIP - Universitas Riau, 2026)
Interpretation important to help students understand the meaning behind information. With this ability, students can assess, interpret, and connect concepts more deeply. this research aims to describe the cultivation of categorization in IPAS learning at Madrasah Ibtidaiyah, to describe the cultivation of decoding significance in IPAS learning at Madrasah Ibtidaiyah, to explore the cultivation of clarifying meaning in IPAS learning at Madrasah Ibtidaiyah. Type of research: qualitative-ethnographic. Data collection: observation, interviews, and document analysis. Data validity through triangulation of sources and methods. Interactive data analysis. The results of the study indicate that cultivating categorization through strategies, stimuli, and feedback effectively trains students group information, although some are still passive due to differences in experience and motivation. Cultivating the decoding significance with trigger questions, problems, and environmental and inquiry approaches helps students explain concepts in their own words, although some still rely on memorization and need reinforcement through discussion. Cultivating the clarifying of meaning through open questions, re-explanations, and feedback increases student participation, although the skills of comparing information and distinguishing facts from opinions still need to be improved. The cultivation of interpretation in IPAS learning at Madrasah Ibtidaiyah has been implemented and proven to improve student understanding and participation.